A process warehouse based resource suitability evaluation method for business process improvement - Sohail, A. (Institute of Electrical and Electronics Engineers Inc., 2014)
Researches on resource allocations in business process management systems leave an impact to adopt a concrete method for resource performance analysis and evaluations. One established way is a posterior performance evaluation. The ultimate aim in these evaluation methods is identification of most appropriate combination of resources. But, it is found that different types of resources are showing different behavior with the same task. The literature shows that relationship (task to resource) based evaluation of resources is not well understood and use of business process intelligence techniques are not adequately explored. The aim of this research is to present a business process intelligence based resource evaluation method that also provide act of improvement to decision maker. Resources in business process environment are classified into human resources (human agents) and non-human resources (aka tools, machine and software). The two types of resources are not equally similar in behaviors and showing different impact on process performance. This research presents resource classification based evaluation method that identifies a set of relationship between two types of resources and task (named competence, suitability and preference). However, only non-human resource's relationship with task is presented in detail as a resource suitability model. A user guided resources suitability method is developed for the suitability model. Health care case study is used to illustrate the applicability of the method. Â© 2014 IEEE.